Nilai Karakter Islami dalam Kisah Nabi Sulaiman dan Pemindahan Tahta Ratu Balqis: Analisis Pendidikan Qur’ani - Agus Sulistyo; Enik Nur Faizah Nur Faizah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study examines the Islamic character values embodied in the story of Prophet Solomon and the transfer of Queen Bilqis' throne, as narrated in Surah An-Naml, verses 38–40. The focus is to explore the Qur’anic educational messages within the story and to analyze their relevance to character development in contemporary Islamic education. This research employs a qualitative approach, utilizing a literature review and tafsir (exegesis) analysis methods. The primary sources include the Qur’an and both classical and contemporary tafsir books that discuss the story in depth. The findings reveal that the story of Prophet Solomon encompasses various Islamic character values, including monotheism (tawhid), knowledge, gratitude, just leadership, and a courteous and wise approach to da'wah (Islamic preaching). These values are reflected in the personality of Prophet Solomon, who possessed high intellectual and spiritual aptitude, as well as in the figure of the servant who was able to transfer the throne by Allah’s permission through the knowledge he had. These findings affirm that the story of Prophet Solomon is relevant as a source of learning for the development of a Qur’an-based character education curriculum. These values have the potential to instill a holistic Islamic character, not only cognitively but also affectively and psychomotorically. In the context of globalization and moral degradation among the younger generation, this story can serve as an inspiring and applicable teaching material in Islamic education. This study offers both theoretical and practical contributions to the development of a more value-oriented Islamic education curriculum.